Trade conflicts with side effects: Compensation for innocent bystanders when imposing punitive tariffs - Gabriel Felbermayr; Christoph Herrmann (Stiftung Familienunternehmen, 2020)
The punitive tariffs and countervailing customs duties imposed by the USA lead to substantial competitive disadvantages for family businesses in Europe. A study commissioned by the Foundation for Family Businesses draws the conclusion that the trade disputes between the USA and the European Union are meanwhile spilling over to industries that have nothing to do with the original trade conflict. Family companies are affected the most by countervailing customs duties imposed by the USA.
Keywords: 330